Berteologi yang humanis: Membangun spiritualitas kesetaraan di antara perbedaan pandangan teologis - Afaradi, Asep (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
The phenomenon of theology in the digital space has shown a worrying escalation, where pastors, theologians, or those who call themselves apologists tend to be condescending; they often label each other